Evaluasi Model CIPP pada Kurikulum Sekolah Dasar Islam Terpadu - Warsono Warsono (Medan Resource Center, 2023)
This study evaluated the integrated Islamic learning system using the CIPP model. The objectives of this study were to (1) understand the background, input, integrated Islamic learning process, and determine the success parameters of the system. The research employed a qualitative approach utilizing the CIPP model for evaluation. Data analysis techniques involved simultaneous cross-section and data interpretation. The findings demonstrated that the integrated Islamic learning system can foster character development and enhance student achievement across various dimensions, including context, input, process, and product. The outcomes include: (1) The background of the integrated Islamic school learning system emphasizes actualizing Islamic civilization for the next generation, (2) The registration process comprises two stages, including assessments related to psychology, basic literacy, and the Qur'an, (3) The implementation of the integrated Islamic school system for character development involves daily habits and self-improvement activities, (4) In terms of character enhancement and student achievement, students are capable of applying Islamic teachings in their daily activities, and the parameters of graduation success are met at preferred schools.